FAKTOR-FAKTOR YANG MEMPENGARUHI KEIKUTSERTAAN IBU DALAM PELAKSANAAN KELAS IBU HAMIL: FAKTOR-FAKTOR YANG MEMPENGARUHI KEIKUTSERTAAN IBU DALAM PELAKSANAAN KELAS IBU HAMIL - Andriani, Lusi; Ratna, Karina Dwi; Mariati, Mariati (JURNAL MEDIA KESEHATAN, 2023)
Data from the World Health Organization (WHO) for 2020 pregnant women class activities in each health center. The aim of the research is to know the factors that influence the participation of mothers in the implementation of classes for pregnant women in the working area of ??the Kandang Health Center in Bengkulu City. This type of research is an analytic descriptive research with a cross-sectional research design approach. The population in this study were all pregnant women with gestational age ? 37 weeks in the Working Area of ??the Kandang Health Center from January 2023 to February 5 2023 as many as 43 pregnant women, using a total sampling technique. The result of adequate knowledge is 62,8%, husband's support is 55.8%, multipara/grande parity is 60.5%, 53.5% is with low economy, pregnant women class participation is not active as much as 65.1%. The results of the bivariate analysis test obtained a p-value = ? ? 0.05 which showed that there was a significant relationship between knowledge, husband's support, parity, and the economy. In multivariate analysis, the most dominant factor was parity in the mother. It is suggested to holders of the pregnant women class program to provide more interesting, innovative and adaptive material. Create a whatsapp group to provide info, remind you of the schedule. Provide social support husband or other family.